An Evaluation of the Impact of Deep Breathing Exercises on Reducing Academic Stress in B.Sc. Nursing Semester Students - Reny Thomas; Anjali Samson; Khushi; Bharti; Aneesha; Disha; Jasmine; Nikita; Monika; Sheetal; Tanu (International Journal of Evidence Based Nursing And Practices, 2024)
Introduction: Academic stress nowadays is one of the considerable problems in nursing students which need to be tackle for improvement of their profession. Objectives: The objectives of the study were a) To assess level of stress among 3rd semester and 4th semester BSc Nursing students (b) To assess the effectiveness of selective self-help technique among 3rd semester and 4th semester B.sc Nursing students, (c) To compare pre-test and post-test score regarding the effectiveness selective self-help technique on stress among 3rd semester and 4th semester BSc Nursing students, (d) To investigate the relationship between pre-test scores and demographic variables, a quantitative research approach was employed in this study. Methods and Methodology:A sample of 98 B.Sc. nursing students in their semester was chosen using a convenience sampling method. The study utilized a modified academic stress scale as its instrument. A preliminary study was conducted to assess the viability of the research. Result and conclusion: The result of study revealed that majority (83.67%) of nursing students had stress, (mild stress 45.92% (45) and 25.51% (25) had moderate stress and 12.24% (12) had severe stress). Mean pre-test score was 73.0306 and the standard deviation was 31.3399, mean post-test score was 27.8163 and the standard deviation was 18.1763. The mean difference score was 45.2143. Z Value 12.36 and higher than table value (z=1.98) at 0.05 level of significance. This suggests that the demonstration successfully lowered the academic stress levels among nursing students.
Keywords: Academic stress; Moderate stress; Preliminary study; Self-help technique; nursing students